A simple empirical formula of origin intensity factor in singular boundary method for two-dimensional Hausdorff derivative Laplace equations with Dirichlet boundary. (1st September 2018) - Wang, Fajie; Chen, Wen; Hua, Qingsong
Abstract: This paper presents a simple empirical formula of origin intensity factor in singular boundary method (SBM) solution of Hausdorff derivative Laplace equations. The SBM with the empirical formula is mathematically more simple and computationally more efficient than using the other techniques for origin intensity factor. Numerical experiments simulate the steady heat conduction through fractal media governed by the Hausdorff Laplace equation, and show the efficiency and reliability benefits of the present SBM empirical formula.